SUPPORT VECTOR MACHINE METHOD FOR PREDICTING INVESTMENT MEASURES - Olga V. Kitova; Igor B. Kolmakov; Ilya A. Penkov (Статистика и экономика)
Possibilities of applying intelligent machine learning technique based on support vectors for predicting investment measures are considered in the article. The base features of support vector method over traditional econometric techniques for improving the forecast quality are described. Computer modeling results in terms of tuning support vector machine models developed with programming language Python for predicting some investment measures are shown.